Language practices and performance in English among High School Pupils of Kisii South Kenya / Jackline Kerubo Ntabo and Ogone John Obiero - Jackline, Kerubo Ntabo; Ogone, John Obiero (Universiti Teknologi MARA, Kedah, 2017)
The overriding purpose of this paper is to describe language practices and to determine whether the practices account for performance level in English language in Kisii South schools. The performance of English language in Kenya Certificate of Secondary Education exam (henceforth KCSE) in Kisii South Sub County has been rated low. For instance, in the year 2012 and 2013, the sub-county registered low mean scores of 4.74 and 4.39 respectively out of a maximum score of 12. These results have caused concern because English is both medium of instruction and compulsory subject in all Kenyan public schools. The national syllabus emphasizes the core status of English but it appears schools implement this policy at different levels, possibly causing varying overall school performance and the performance in English language. Stratified random sampling was used to select 3 good performing schools, 3 average performing and 3 poor performing schools for the study based on their KCSE performance in English. A total of nine schools were selected for the study. An equal number of 60 pupils were selected randomly from each school to fill out questionnaires. Interview schedules with heads of department of languages and principals were also carried out. In addition, an observation schedule was applied after the questionnaires had been sent out for cross checking purposes. Data was analyzed within the framework of Language Management Theory. The results indicate that school language practices affect performance in English in the sampled schools; a situation that could go a long way in determining overall school performance in Kisii South Sub County.